Implementation of the Family Hope Program Complete Poverty in Gorontalo City - Fatra Abdullah; Abdul Rahmat; Icam Sutisna (Global Scientific Publishing, 2023)
This study aims to determine the process of implementing the Keluarga Harapan Program in overcoming poverty in Kota Tengah Sub-district, Gorontalo City and what factors have become obstacles to PKH in overcoming poverty in Kota Tengah Subdistrict, Gorontalo City. The research uses a qualitative descriptive method. The data collection techniques include observation, interviews, and documentation. The results showed that the Keluarga Harapan Program has been running relatively optimally. This can be seen from the community who have experienced a fairly positive impact of this program, especially getting a spouse who is committed and honest. The mechanism for disbursing assistance is following the applicable SOP (Operational Standards ). However, there are several obstacles in its participation and cooperation of beneficiary families and PKH assistants, and a lack of resources.
Keywords: Implementation; Communication; Poverty